Problems to Consider Before Determining the Regimen of the Treatment for Juvenile Systemic Sclerosis Treatment: A Case Report Where Tocilizumab Monotherapy Succeeded Efficiently and Safely. Issue 15 (February 2022) - Funauchi, Masanori; Kinoshita, Koji
Juvenile systemic sclerosis (SSc) is a rare condition that results in various disorders, including growth retardation and learning disabilities in addition to impaired quality of life due to fibrosis and microvascular disorders in multiple organs. Recently, efficacies of immunosuppressants such as cyclophosphamide and mycophenolate mofetil, as well as biological agents, have been reported in adult patients with SSc. However, there has been no consensus in the treatment of juvenile SSc due to its rarity and the fact that skin sclerosis may be self-limiting in some patients. Here, we present a case of 13-year-onset SSc with growth retardation and learning disabilities, in addition to skin sclerosis, interstitial lung disease, and possible myocardial fibrosis that was successfully treated with tocilizumab monotherapy without remarkable adverse reactions. As careful case-by-case management of patient's growth and education along with standard treatment is needed, the documentation of such case is important for the evaluation of the efficient and safe therapy for juvenile SSc.